THE EFFECTIVENESS OF PEDAGOGICAL DESIGN BASED ON THE COGNITIVE APPROACH IN MUSIC LESSONS - Tolibjanova Ikboloy Tokhirjon kizi (Bright Mind Publishing, 2025)
This article explores the theoretical and practical aspects of pedagogical design based on the cognitive approach in music lessons. It analyzes the essence of cognitive pedagogy, its integration into music education, and the possibilities for enhancing students’ cognitive activities through this approach. The article also discusses the stages of pedagogical design, indicators of effectiveness, and key principles necessary for higher pedagogical education institutions to improve the quality of education.
Keywords: Cognitive approach, pedagogical design, music lessons, cognitive activity, competency-based education, developmental education, aesthetic education, individual approach, educational effectiveness, metacognitive strategies.